2006
DOI: 10.1016/j.contraception.2006.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Fourteen-day safety and acceptability study of 6% cellulose sulfate gel: a randomized double-blind Phase I safety study

Abstract: TitleFourteen-day safety and acceptability study of 6% cellulose sulfate gel: a randomized double-blind Phase I safety study Abstract Background: Topical microbicides against the human immunodeficiency virus (HIV) 1 that are nonirritating to the female genital epithelium are urgently needed to slow the heterosexual spread of HIV infection. Products that are also effective contraceptives provide additional benefits. Cellulose sulfate (CS) is a noncytotoxic antifertility agent that exhibits in vitro antimicrobia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
59
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 17 publications
1
59
0
Order By: Relevance
“…12 In the present study, CS use was associated with increases in E. coli and Enterococcus. The reduction of SLPI and MPO after CS use may explain the relative overgrowth of E. coli and Enterococcus.…”
Section: Vaginal Safety Of Cs Hec Placebo and N-9mentioning
confidence: 70%
See 3 more Smart Citations
“…12 In the present study, CS use was associated with increases in E. coli and Enterococcus. The reduction of SLPI and MPO after CS use may explain the relative overgrowth of E. coli and Enterococcus.…”
Section: Vaginal Safety Of Cs Hec Placebo and N-9mentioning
confidence: 70%
“…12 However, CS was associated with a decrease in the protective factor SLPI, a parameter not assessed in earlier CS studies. A similar effect was seen in early trials of other microbicide candidates later found in Phase III trials not to be effective.…”
Section: Vaginal Safety Of Cs Hec Placebo and N-9mentioning
confidence: 94%
See 2 more Smart Citations
“…In another CS gel study, 44% of the women in the sexually abstinent group and 18% in the CS sexually active group reported that leakage would prevent them from using the gel in the future (101). In a separate study, the author noted that reformulating the gel to reduce leakage could lead to increased irritation (102).…”
Section: Semisolids-hydrogelsmentioning
confidence: 99%